2023
DOI: 10.1002/fsn3.3216
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MSTN/Smad signaling pathway genes and its association with meat quality in Tibetan sheep (Ovis aries)

Abstract: Tibetan sheep is a unique breed living in Qinghai‐Tibet Plateau. Since MSTN/Smad signaling pathway plays a critical role in the regulation of muscle development, we aimed to study the mutton quality, mRNA expression of main transduction genes in the MSTN/Smad signaling pathway, and the effects of those genes on the mutton quality of Tibetan sheep in this study. Six‐month‐old Qinghai‐Tibetan sheep were selected, slaughtered, and their Longissimus lumborum, semitendinosus muscle, arm triceps, and quadriceps femo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…We speculated that the miR-10 family is tightly regulated by muscle fiber transformation. The target genes of the miR-10 family in the ceRNA network included DES [ 20 ], MYBPH [ 21 ] and SMAD3 [ 22 ]. To verify this hypothesis, we constructed MYBPH wild-type (WT) plasmids and mutantion (MUT) plasmids for co-transfection with miR-10a-5p mimics, and dual luciferase reporter genes determined that miR-10a-5p and MYBPH had strong binding ability (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We speculated that the miR-10 family is tightly regulated by muscle fiber transformation. The target genes of the miR-10 family in the ceRNA network included DES [ 20 ], MYBPH [ 21 ] and SMAD3 [ 22 ]. To verify this hypothesis, we constructed MYBPH wild-type (WT) plasmids and mutantion (MUT) plasmids for co-transfection with miR-10a-5p mimics, and dual luciferase reporter genes determined that miR-10a-5p and MYBPH had strong binding ability (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Polyunsaturated fatty acids have been shown to affect energy metabolism in liver and fat cells, leading to reduced fat accumulation [ 35 ]. Similarly, according to He et al, it was found that reduced MSTN resulted in increased levels of polyunsaturated fatty acids, especially arachidonic acid, in rams [ 41 ]. Consequently, the increased content of polyunsaturated fatty acids such as arachidonic acid and linoleic acid in our study may contribute to the observed decrease in fat deposition resulting from MSTN mutation.…”
Section: Discussionmentioning
confidence: 99%